OPTIMALISASI PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN BANDENG (Chanos chanos) MELALUI SUPLEMENTASI MINYAK ZAITUN PADA PAKAN KOMERSIL - Putriani, Herni; Lumbessy, Salnida Yuniarti; Mukhlis, Alis (Journal of Fish Nutrition, 2024)
This study aims to evaluate the effect of olive oil supplementation in commercial feed on the growth and survival rate of milkfish (Chanos chanos) fry. The research used a Completely Randomized Design with five treatments and three replications: control without oil addition (A), fish oil 1 ml/30 g feed (B), olive oil 0.5 ml/30 g feed (C), olive oil 1 ml/30 g feed (D), and olive oil 1.5 ml/30 g feed (E). The results showed that olive oil supplementation significantly affected growth and survival (p<0.05). Treatment D (olive oil 1 ml/30 g feed) demonstrated the best performance with absolute weight growth of 0.40 g, relative weight growth of 366.7%, specific daily weight growth rate of 3.48%/day, and relative length growth percentage of 172.2%. This treatment resulted in the highest survival rate of 86.7%. These values were significantly higher compared to other treatments, including fish oil supplementation. These findings indicate that olive oil supplementation at a dose of 1 ml/30 g feed can effectively optimize the growth and survival of milkfish fry, and has the potential to become a sustainable alternative to fish oil in aquaculture feed formulations.